Synthesis, Characterization, and Crystal Structure of [N′-(3-Ethoxy-2-hydroxybenzylidene)-4-fluorobenzohydrazido](quinolin-8-olato)oxovanadium(V). Issue 1 (2nd January 2016) - Sheng, Gui-Hua; Cheng, Xiao-Shan; You, Zhonglu; Zhu, Hai-Liang
Abstract : A new oxovanadium(V) complex, [ N '-(3-ethoxy-2-hydroxybenzylidene)-4-fluorobenzohydrazido](quinolin-8-olato)oxovanadium(V), [VO(EFH)(QN)], where EFH is the anion of N '-(3-ethoxy-2-hydroxybenzylidene)-4-fluorobenzohydrazide, and QN is the anion of 8-hydroxyquinoline, was prepared and characterized by elemental analysis, infrared spectra, thermal analysis and single-crystal X-ray diffraction. The complex crystallizes in the monoclinic space group P 21 / n, with unit cell dimensions a = 8.3921(4) Å, b = 28.200(1) Å, c = 10.0237(5) Å, β = 102.394(1)°, V = 2316.9(2) Å 3, Z = 4, GOOF = 1.101, R 1 = 0.0464, and wR 2 = 0.1081. The V atom is coordinated by the three donor atoms of EFH and two donor atoms of QN, as well as one oxo oxygen group, forming an octahedral coordination.